Manajemen Kepala Sekolah SMA PGRI 1 Jombang - Shefy Badrul Lailiyah; Waslah - - (JoEMS (Journal of Education and Management Studies), 2020)
This study aims to describe the implementation of the participation of the Principal's management in SMA PGRI 1 Jombang. The implementation of the Principal's form of management is known by analyzing primary and secondary data in SMA PGRI 1 Jombang. This research uses descriptive qualitative design. The data analyzed are data from the main source of this study, namely the principal, besides the analyzed data are data in the form of writing, such as a brief history of SMA PGRI 1 Jombang, and other documents related to research. The results of the study were analyzed using Presistant techniques (persistence of observation) and Triangulation (combining various data collection techniques). The results of the study stated that the implementation of school principal management in SMA PGRI 1 Jombang is in accordance with Law No. 20 of 2003 which is able to guarantee equal opportunity for education, quality improvement and relevance and efficiency of education management to face challenges in accordance with the demands of changing local, national, and global. The role of the principal's management is very positive, both for the school, for the teaching performance of teachers, the performance of staff and employees as well as for students. This form of headmaster management involves all components, both students, educators, and education staff.